Growing Up with America : Youth, Myth, and National Identity, 1945 to Present - Murphy, Emily A., 1987- (Book collections on Project MUSE., 2020)
"Growing Up with America is a study of the relationship between national myths and the figure of the child, using young adult literature and American studies scholarship. Murphy considers how a set of Cold War-era literary critics used the child to give shape to abstract ideas regarding national identity. Known as myth and symbol critics, they found specific recurring themes in American literature and culture they believed helped forge American national identity. While partially intended to bolster national pride during the Cold War, this myth-gathering also represented each critic's individual attempt to the answer the question: "What does it mean to be an American?" Their work was thus representative of a search for a national narrative that could satisfactorily answer this question. They drew upon cultural conceptions of childhood such as innocence and vulnerability in order to better explain the divine mission of the United States during the tumultuous post-WWII period, and, in doing so, made innocent the colonial exploits of a nation that has resisted being labeled an empire. This project therefore takes as its point of departure the creation and validation of national myths that emerged from the myth and symbol school and charts the literary response to these myths from the 1950s to the present. Murphy uses a variety of types of sources, from newspapers, to 1940s literary criticism, to American Studies scholarship, to contemporary literature. She looks at literature both produced for and by children and young adults, as well as literature which features children and young adults as main characters. Her work complicates the traditional views of children in the US in terms of race, gender, and sexuality. She pushes the boundaries of young adult literature and discusses mainstream classic and contemporary titles that feature young adults (Vladimir Nabakov's Lolita, Karen O. Russel's Swamplandia!; Jeffrey Eugenides's The Virgin Suicides); works published prior to the formal establishment of the YA genre (Scott O'Dell's Island of the Blue Dolphins, J.D. Salinger's The Catcher in the Rye); and seminal young adult books that shook the genre out of complacency (M.T. Anderson's Feed, Leslie Marmon Silko's Gardens in the Dunes)"--